THE ANALYSIS OF STUDENTS’ PROBLEM IN SPEAKING ENGLISH AT THE GRADE XI OF SMK NEGERI PERTANIAN PEMBANGUNAN TAPANULI SELATAN - Ritonga, Hartika Rini (jurnalalfa, 2024)
This study was aimed to find out the Speaking Problem at the Grade XI SMK Negeri Pertanian Pembangunan Tapanuli Selatan. The objective of this research is to find out students’ problems in learning English speaking skill. The design of the research is by using descriptive qualitative method. The subject of this research is the students’ of grade XI SMK Negeri Pertanian Pembangunan Tapanuli Selatan.The data of this research were collected by using test, observation, interview, and documentation. From the finding and discussion, the students have problem in speaking. The problems were consisted of grammar, shyness, vocabulary and meaning, pronunciation, lack of confident, fear of making mistake, and anxiety. From the problems the dominantly problems is pronunciation. Most of them stated that they afraid speak because they do not know how many vocabulary and to pronounce the words. They were afraid if they made a mistake in term of pronouncing the words and using the vocabulary.